CPWF Medium Term Plan (2009-2011) - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2008)
This Medium Term Plan (MTP) is written as the CPWF transitions from the first five years of operation to the second phase commencing in 2009. It describes the status of the CPWF as the newly established Board discusses and approves plans for the CPWF second five year term. The CPWF also felt it appropriate to time this version of the MTP to coincide with the Second International Forum on Water and Food, held from 10-14 November 2008. We consider the Phase 2 planning process a highlight of the CPWF 2008 programmatic achievements along with the many results coming out of the initial research portfolio that has fed into the plans contained in this document. In parallel has been the exploration of structures and procedures for the program that will best take the CPWF research agenda forward. The CPWF’s External Review (CPER) Panel provided valuable advice and recommendations for the transition, as did the commentaries on the CPWF’s Phase 2 plans by IWMI and many other partners including ExCo, the Science Council (SC) in addition to the CPWF Consortium Steering Committee (CSC). Key components of the vision and implementation plans include · Focus on six river basins rather than nine. · Added focus on the most successful content of Phase 1. · Priority Development Challenges in each basin. · Establishment of ‘Topic Working Groups’. · Increased presence of CPWF within each basin. · Enhanced and purposive network building in each basin. · Streamlined governance. · Simplified management and reporting structures. This section provides an overview of these changes. In subsequent sections, we outline each of the seven MTP projects that are the basis of CPWF’s Second Phase. These are the six initial ‘Basin Development Challenges’ with a seventh describing the ‘Cross Basin Learning’ aspects of the program.